A Collaborative Control of Brain Computer Interface and Digital Locker - D.r.S.Anthoniraj, V. Hemanth Kumar, S.Hariharan, S.Mohanbabu, R.Dinesh Kumar (International Journal of Advanced Science and Technology, 2020)
This paper presents another plan in teaming up non-intrusive cerebrum PC interface (BCI) and a computerized storage. The BCI framework actualizes consistent state visual evoked potential (SSVEP) technique that concentrates highlights from electro-encephalography (EEG) flags in deciding the expectations or orders from human-mind. The grouping of EEG signals uses channel bank as per recurrence of the boosts visual. The client goals, which are to move "Open", "Close" are worked together with an insightful Locker framework . Exploratory outcomes are directed to show the viability of the proposed strategy. In light of most extreme a posteriori likelihood (MAP), this strategy builds up the probabilistic models of human and robot control orders to understand the ideal control of a mind activated shared control framework. Application on an insightful Bayesian shared control framework dependent on consistent state visual evoked potential (SSVEP)- based cerebrum machine interface (BMI) is introduced forever nonstop wheelchair route task. In addition, to get increasingly exact mind control orders for shared controller and adjust the proposed framework to the vulnerability of electroencephalogram (EEG), a various leveled cerebrum control component with criticism rule is structured. The goal of the task is to make cerebrum secret phrase which can be constrained by utilizing mind waves utilizing Mindwave EEG terminals